Food habits and consumption in developing countries : manual for field studies - Hartog, A. P. den; Brouwer, Inge D.; Staveren, Wija A. van (Wageningen Academic Publishers, 2006)
Deals with the process of changing food habits and consumption patterns in developing countries. This work discusses the nutritional implications, together with practical information, in relationship to conducting field surveys. It provides insight into the dynamics of food habits and consumption and its socio-economic and cultural dimensions